Towards Next Generation Cleaning Tools: Factors Affecting Cleaning Robot Usage and Proxemic Behaviors Design - Chen, Yuhao; Luo, Yue; Hu, Boyi (Frontiers in Electronics, 2022)
Among all healthcare sectors and working processes, the janitorial section is a prominent source of work-related injuries due to its labor-intensive nature and rising need for a hygienic environment, thus requiring extra attention for prevention strategies. Advancement in robotic technology has allowed autonomous cleaning robots to be a viable solution to ease the burden of janitors. To evaluate the application of commercial-grade cleaning robots, a video-based survey was developed and distributed to participants. Results from 117 participants revealed that: 1) participants were less tolerant when their personal space was invaded by humans compared with the cleaning robot, 2) it’s better to inform the surrounding humans that the cleaning robot has been sanitized to make them feel safe and comfortable during the pandemic, and 3) to make the interaction more socially acceptable, the cleaning robot should respect human personal space, especially when there is ample space to maneuver. The findings of the present study provide insight into the usage and Proxemic behaviors design of future cleaning robots.